Analysis of Application of the Thermostat in the Cooling System of the Nissan CWB 45 Dump Truck Engine - Suryapradana , Ilmawan; Halim, Arfan (STMIK Widya Cipta Dharma, 2024)
The cooling system in vehicle engines ensures that the engine operates within an ideal temperature range, maintaining optimal performance. In the Nissan CWB 45 Dump Truck engine, the target coolant temperature ranges between 80°C and 90°C. This study evaluates the performance of the thermostat in the engine cooling system and its impact on engine temperature at varying engine speeds. Testing involved measuring the coolant temperature at engine speeds of 560 rpm, 1000 rpm, and 1500 rpm, with readings taken at intervals of 5, 10, and 15 minutes. The results indicated that at 1500 rpm, the coolant temperature reached 67.7°C after 15 minutes, which was insufficient to fully activate the thermostat. At 1000 rpm and 560 rpm, the temperatures were 61.7°C and 54.1°C, respectively, also below the thermostat activation threshold. These findings demonstrate that higher engine speeds result in faster temperature increases, enabling quicker thermostat activation. However, achieving the optimal temperature range requires improvements in the cooling system's design and component quality. This study provides valuable insights for enhancing the maintenance and performance of cooling systems in heavy vehicles, particularly those operating in demanding environments such as mining areas.